Implementasi Arsitektur Mikroservis dan Orkestrasi Kubernetes dengan Paradigma DDD pada Website Freelancing - Farhana, Hafi Ihza; Mumpuni, Retno; Ali Akbar, Fawwaz (UNIVERSITAS RAHARJA, 2025)
The rapid development of the digital era triggered by COVID-19 has changed the way people earn income, with more and more people turning to freelance work. M-Knows Consulting responded to this change by creating a website-based freelance platform, designed to be a place for Indonesian freelancers to develop their careers. Given the complexity of the system and the high interaction of various users, a more modular development is needed to increase efficiency, especially in handling diverse project challenges. Therefore, a microservice architecture was chosen as a more appropriate solution than a monolithic architecture. The design of this microservice architecture involves several important steps, including the application of the Domain-Driven Design (DDD) paradigm with the principle of bounded context to clearly separate business domains and implement a multi-database approach that suits the specific needs of each service. The deployment process will be carried out using Kubernetes to manage the workload of each microservice and ensure system scalability and reliability. With this approach, it is hoped that the development of a website-based freelance platform can run more efficiently and quickly, so that it can immediately provide optimal services for freelancers in Indonesia.